Associations of maternal PM2.5 exposure with preterm birth and miscarriage in women undergoing in vitro fertilization: a retrospective cohort study - Miaoxin Chen; Qiaoyu Chen; Gengze Liao; Chunyan Sun; Cong Liu; Xia Meng; Wentao Li; Andong Qiu; Orhan Bukulmez; Haidong Kan; Feng Wang; Lap Ah Tse; et al. (Frontiers in Endocrinology)
BackgroundExcessive exposure to PM2.5 can be detrimental to reproductive health. The objective of this study was to investigate the potential associations between ambient PM2.5 exposure during different periods and negative pregnancy outcomes, such as miscarriage and preterm birth, in patients who underwent assisted reproductive technology (ART).MethodsThis retrospective cohort study examined the outcomes of 2,839 infertile women aged ≤ 45 years who underwent their first fresh or frozen-thawed embryo transfer at the Shanghai First Maternity and Infant Hospital between April 2016 and December 2019. Satellite data were used to determine the daily average levels of PM2.5, and exposure was categorized as excessive if it exceeded the WHO’s interim target 2 level of 50 µg/m3. The analysis was conducted separately for seven different periods. Our study used multinomial logistic regression models to explore the potential associations between PM2.5 exposure and adverse pregnancy outcomes. Sensitivity analysis was conducted by excluding women who underwent blastocyst transfer.ResultsDaily PM2.5 exposure exceeding the threshold (50 µg/m3) was associated with an increased risk of miscarriage during the period after confirmation of clinical pregnancy or biochemical pregnancy, with adjusted odds ratios (AORs) of 2.22 (95% CI 1.75-2.81) and 2.23 (95% CI 1.68-2.96), respectively. Moreover, for each increase of 10 µg/m3 above the threshold for PM2.5, there was a 46% elevated risk of preterm birth (AOR = 1.46, 95% CI 1.09-1.94) during the period after the confirmation of clinical pregnancy and a 61% elevated risk of preterm birth (AOR = 1.61, 95% CI 1.16-2.23) during the period after the confirmation of biochemical pregnancy. Our stratified analyses revealed that women with an endometrial thickness <11 mm or who underwent frozen embryo transfer were more vulnerable to PM2.5 exposure, leading to higher rates of preterm birth.ConclusionExcessive PM2.5 exposure after biochemical pregnancy or clinical pregnancy was associated with increased risks of preterm birth and miscarriage among women who underwent ART.